Pengaruh Social Media Marketing, Store Environment, Sales Promotion, dan Perceived Value Terhadap Purchase Decision Konsumen SOGO Department Store - Priandy Yaputra (Universitas Tarumanagara, 2020)
This research was conducted to determine the effect of social media marketing, store environment, sales promotion, and perceived value to purchase decision SOGO Department Store. This research uses a quantitative method that is by distributing questionnaires to 100 respondents who have bought goods at SOGO in West Jakarta. The research method in this study used multiple regression analysis assisted by SPSS. The results of this study are known that simultaneously all independent variables have an influence on purchase decision. Partially, the variables of the store environment, sales promotion, and perceived value have a significant influence on consumer purchase decision, while the social media marketing variable do not significantly influence consumer purchase decision.